ENGLISH LANGUAGE PROFICIENCY IN ACTUARIAL EDUCATION QUALITY IMPROVEMENT: CHALLENGES AND OPPORTUNITIES IN UKRAINE - Fursenko , Tetiana; Druz, Jurii; Druz, Galyna (Physical and Mathematical Education, 2022)
Formulation of the problem. The paper is a contribution to the discussion of the importance of English proficiency for the actuarial profession in the present-day globalized world. Given the fact that the system of actuarial education in Ukraine is currently at the stage of its formation and hence relies greatly on the international standards set by actuarial organizations, we hypothesize that an English language is an effective tool of professional advancement not only for qualified professionals but also for aspiring actuaries. The study aims to investigate interdependencies between good English skills, the development of actuarial education in Ukraine, and attaining internationally recognized actuarial credentials by Ukrainian actuarial candidates as well as the promotion of the profession of an actuary in the country. Materials and methods. The current research utilizes the qualitative methods of the pedagogical theoretical analysis (curricula, legislative documents, scientific resources) and observations illustrating the practice of actuarial professionals` training in Ukraine and as well as the analysis of international actuarial organizations` internal reports and documents; the authors also employ the synthesis of pedagogical knowledge to draw up some practical recommendations on the improvement of actuarial education in Ukraine. Results. The paper is one of the first comprehensive attempts to analyze the role of English proficiency in aspiring actuaries` professional development in Ukraine and to work out some recommendations on the issue. Based on the analysis of the relevant sources we have identified that English mastery can bring the actuarial profession and education in Ukraine to a qualitatively new level. However, English skills are not considered to be a priority at the level of the national educational norms and regulations. We suggest that possible ways out are improved English instruction, cooperation with international actuarial organizations, and forming psychological readiness in delegates and professionals to speak professional English publicly.Conclusion. The role of English competence for actuarial professionals in Ukraine should be prioritized since the profession itself is regulated by the international standards guiding particular eligibility criteria to be recognized by the word actuarial community as a qualified actuary worldwide. We believe that the proposed recommendations will improve actuarial professional education and the existing language training and will help to bring the profession in general to a qualitatively new level.
Keywords: actuaries; actuarial education; English proficiency; international actuarial organizations; recommendations